Emotional and mental well-being talk: stress management / Seng Hui Zanne and Muhammad Usamah Mohd Ridzuan - Seng, Hui Zanne; Mohd Ridzuan, Muhammad Usamah (Academy of Language Studies, 2023)
The French Language Club of Universiti Teknologi MARA Cawangan Pulau Pinang held its first virtual emotional and mental well-being talk via Google Meet on the 5th of December 2022 from 6:00 p.m. to 7:00 p.m. The main purpose of the talk is to raise awareness among university students on the importance of mental well-being. A registered and licensed counsellor, Miss Lee Phei Wei has been invited as a guest speaker to share her professional thoughts on stress management. She graduated with a Masters in Counselling Psychology from Universiti Malaysia Sabah, and has been working in this field for more than five years. She has had experiences working with multinational clientele and public community, focusing on emotion regulation and bereavement.